DERMATOFIBROSARCOMA PROTUBERANS --A RARE VARI^ANTOF SOFT TISSUE SARCOMA OF SKIN. AN EXPERIENCE OF TWO CASES AT AYUB TEACHING HOSPITAL COMPLEX (ATHC), ABBOTTABAD - Mufti, Tariq; Khan, M. Saeed; Dua, Muzher -U-; Waqar, Farah (Journal of Ayub Medical College Abbottabad, 2001)
An old lady of 58 years' age presented with a huge soft tissue mass over left pectoral region which was gradually increasing in size over the last 5-ycars. Patient also gives history' of recent appearance of constant dull pain and low grade fever (<100Fo) for the last 3-4 months. CT Scan revealed a soil tissue sub cutaneous mass extending from the dermis downwards without rib erosion. X-Ray chest clear and USG abdomen was normal. Excisional biopsy revealed Dermatofibrosarcoma protuberans. After wound healing, external radiation on 10Mev electron beam (Varianclinac-20) with direct anterior field encompassing nearly upper 2/3 of left chest wall and delivering a tumor dose of 48 grays at I cm depth in 16 treatments. 3 'A weeks' time as Ïµ 300 cgys daily. The tumor bed can be radiated on cobolt -60 (Mega voltage beam) with tangential fields to mid line dose of 60 grays in 30 fractions for 6 weeks